UPAYA MEMBANGUN EPISTEMOLOGI ISLAM (Studi Pada Pembelajaran Buku âOur Philosophyâ di RausyanFikr Yogyakarta) - Efendy, Rustan (P3M STAIN Parepare, 2016)
RausyanFikr Institute is an agency of the study and publication of the book lies in Kaliurang Yogyakarta. The institute focuses on the study of philosophy and Islamic thought. Study participants were students from various regions in Indonesia. In this study, the authors focused on building the Islamic epistemology through the book âOur Philosophyâ by Baqir Sadr, an Iraqi cleric concerned about world issues and an architect revolutionary thinking. This book thoroughly dissected in RausyanFikr Institute and has been a curriculum epistemology at the agency. The author will show the opinion epistemology Baqir Sadr to view some Western thinkers such as Plato, Descartes, Immanuel Kant, and John Locke. He himself offered his thoughts as he constructions as âdisposesionâ (nazhariyah intizâÄ).